2007
DOI: 10.1007/s12122-007-9039-5
|View full text |Cite
|
Sign up to set email alerts
|

Transformational Leadership in Labor Organizations: The Effects on Union Citizenship Behaviors

Abstract: Transformational leadership, Labor organizations, Union citizenship,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 41 publications
6
42
0
2
Order By: Relevance
“…Relying on organizational support theory (Eisenberger et al, 1986;Eisenberger and Stinglhamber, 2011), we argue that, because the leader represents the organization, his/her transformational leadership is indicative for subordinates of the favorable treatment received by the organization, leading to higher perceived organizational support (POS) and, finally, affective commitment. In this respect, we extend the work of Twigg et al (2008) who showed that perceived union support mediates the relationship between transformation leadership of the union steward and commitment to the union.…”
Section: The Influence Of Transformational Leadership On Followers' Asupporting
confidence: 61%
“…Relying on organizational support theory (Eisenberger et al, 1986;Eisenberger and Stinglhamber, 2011), we argue that, because the leader represents the organization, his/her transformational leadership is indicative for subordinates of the favorable treatment received by the organization, leading to higher perceived organizational support (POS) and, finally, affective commitment. In this respect, we extend the work of Twigg et al (2008) who showed that perceived union support mediates the relationship between transformation leadership of the union steward and commitment to the union.…”
Section: The Influence Of Transformational Leadership On Followers' Asupporting
confidence: 61%
“…This mediating role of organizational based self-esteem is found to be significant in other organizational settings (Ferris et al, 2009;Lee and Pecce, 2007;McAllister and Bigley, 2002). Twigg et al (2008) also used organization-based self-esteem as an outcome variable of perceived organizational support in their testing of leadership behavior among union members. Based on the aforementioned discussion of the literature, we hypothesize the following proposition.…”
Section: H2mentioning
confidence: 99%
“…For example, in previous studies (Bass, 1997;Conger and Kanungo, 1988), the introduction (to provide a standard determination of characteristics) and result (to determine specific behaviors of leaders) of transformational leadership were determined. These studies failed to implement practical research on other factors in terms of behavior (Twigg and Parayitm, 2007). Greenleaf (1998) suggested the concept of 'servant leadership' as an executive agent of transformational leadership.…”
Section: Introductionmentioning
confidence: 99%